Effect of potential difference between the central and terminal metals on the electron communication in an Fe–Ru–Fe cyanidometal-bridged mixed valence system. Issue 18 (27th July 2022) - Yang, Yu-Ying; Zhu, Xiao-Quan; Wang, Yong; Wu, Xin-Tao; Sheng, Tian-Lu
Abstract : In the Fe–Ru–Fe mixed valence system, the change of the donor and accepter can affect potential difference (energy difference) between bridge and terminal redox centers. This change has an effect on the electron communication. Abstract : A series of trimetallic cyanidometal-bridged compounds with the formula [CpMe x Fe–NC–Ru–CN–FeCpMe x ] n +, N n + ( n = 2, 3 and 4; N = 1, x = 0; N = 2, x = 1; N = 3, x = 3; N = 4, x = 4; N = 5, x = 5), were synthesized and fully characterized. The effect of the potential difference between the central and terminal metals on the electron communication in these trinuclear mixed valence systems was investigated. N 3+ and N 4+ are the one- and two-electron oxidation products of N 2+ . Electrochemical measurements show the presence of electronic interactions between the two terminal Fe atoms. The electronic properties of N 3+ and N 4+ were studied and compared using experimental spectroscopy and time-dependent density-functional calculations. As the number of methyl substituents on the cyclopentadiene ligand increases, the potential difference between the central and terminal redox centers increases and thus, the electron communication between the terminal Fe redox centers or between the neighboring Fe and Ru redox centers becomes weaker. All the mixed valence compounds show localized character.